2009
DOI: 10.1007/s11162-009-9124-0
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Classroom to the Web: Effects of Using New Technologies to Capture and Deliver Lectures

Abstract: Technology expands instructional options for faculty, and this study examines the differential learning effects of offering a lecture on physics to students in a traditional classroom versus internet video formats. Based on an experiment conducted in a natural educational context, results indicate enhanced transfer of lecture information in the video formats relative to the live condition, with students also responding more positively to personalized video presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 26 publications
2
54
0
2
Order By: Relevance
“…Students claim that recordings are just as effective as a live lecture, especially for materials that require increased focus on the content and instructions. 16 Students express increased satisfaction and motivation when courses combine lecture recordings with face-toface instruction. [17][18][19][20] Lecture capture allows students to navigate complex concepts at their own pace, enabling them to clarify confusions and increase their understanding of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Students claim that recordings are just as effective as a live lecture, especially for materials that require increased focus on the content and instructions. 16 Students express increased satisfaction and motivation when courses combine lecture recordings with face-toface instruction. [17][18][19][20] Lecture capture allows students to navigate complex concepts at their own pace, enabling them to clarify confusions and increase their understanding of the material.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, with recent advances in large classroom technology, faculty members can offer students a variety of lecture enhancements. Pharmacy students often have access to lecture handouts and slides, and students now can access audio files, which are available for viewing and downloading after the lecture has taken place.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars often have noted that students positively evaluate the availability of lecture recordings (Dey, Burn, and Gerdes 2009 ;Gosper et al 2007;Green, Pinder-Grover, and Millunchick 2012 ;von Konsky, Ivins, and Gribble 2009 ). Our survey posed a series of questions regarding satisfaction with the lecture-capture technology used in our classes.…”
Section: What Is the Effect Of Viewing Lecture Recordings?mentioning
confidence: 99%
“…However, this raises a relevant pedagogical question: What is the value of students attending class in person? Dey, Burn, and Gerdes ( 2009 ) demonstrated that being in the lecture hall does not guarantee academic success. Utilizing an experimental design, they found that students who watched only video lectures scored better on an exam when compared to those who attended the same lecture in person.…”
Section: Final Course Grades and Group Means By Lecture-capture Viewementioning
confidence: 99%